The Fate of a Gesture : Jackson Pollock and Postwar American Art. - Ratcliff, Carter (New York : Farrar, Straus & Giroux New York, 1996)
Acconci, Vito ; Acker, Kathy ; Africano, Nicholas ; Albers, Josef ; Amaya, Mario ; Andre, Carl ; de Antonio, Emile ; Anuskiewicz, Richard ; Armstrong, Tom ; Astor, Patti ; Avery, Milton ; Baechler, Donald ; Baker, Elizabeth ; Bannard, Walter Darby ; Barr, Alfred H. Jr. ; Barry, Robert ; Baselitz, Georg ; Basquiat, Jean-Michel ; Bauer, Rudolf ; Baziotes, Ethel ; Beaton, Cecil ; Bellamy, Richard ; Benglis, Lynda ; Benton, Maecenas Eason ; Benton, Rita ; Benton, Thomas Hart ; Berkson, Bill ; Bernstein, Roberta ; Bidlo, Mike ; Bierstadt, Albert ; Blesh, Rudi ; Bluhm, Norman ; Blum, Irving ; Bockris, Victor ; Bollinger, Bill ; Boone, Mary ; Borofsky, Jonathan ; Bourdon, David ; Brach, Paul ; Bradley, Peter ; Braque, Georges ; Brauntuch, Troy ; Breer, Robert ; Breton, André ; Brown, James ; Brown, John ; Burckhardt, Rudy ; Burgy, Donald ; Busa, Peter ; Cage, John ; Cahill, Holger ; Calder, Alexander ; Cale, John ; Carey, Ted ; Chamberlain, John ; Chastel, André ; Chia, Sandro ; Church, Frederick E. ; Clemente, Francesco ; Clough, Charles ; Colacello, Bob ; Condo, George ; Cucchi, Enzo ; Cunningham, Merce ; Davis, Stuart ; Denby, Edwin ; Denes, Agnes ; Diller, Burgoyne ; Dine, Jim ; Dubuffet, Jean ; Duchamp, Marcel ; Dzubas, Friedel ; Egan, Charles ; Ernst, Jimmy ; Ernst, Max ; Falkenberg, Paul ; Feeley, Paul ; Feldman, Morton ; Ferren, John ; Fiegan, Richard ; Fields, Danny ; Fishl, Eric ; Riverhead (New York) ; Francis, Sam ; Frankenthaler, Helen ; Fredericks, Tina S. ; Fried, Michael ; Friedman, B.H. ; Gablik, Suzi ; Giacometti, Alberto ; Gibson, William ; Glimcher, Arnold ; Gluck, Nathan ; Goldberg, Michael ; Goldstein, Jack ; Goldzahler, Henry ; Goodman, Job ; Goodnough, Robert ; Gorgoni, Gianfranco ; Gorky, Arshile ; Graham, Dan ; Graham, John ; etc.
Engels
boek
Keywords: Naoorlogse periode; U.S.A.; Verenigde Staten